2020
DOI: 10.1210/clinem/dgaa568
|View full text |Cite
|
Sign up to set email alerts
|

Copeptin Kinetics and Its Relationship to Osmolality During Rehydration for Diabetic Ketoacidosis in Children

Abstract: Context Copeptin is a surrogate marker for arginine vasopressin (AVP) release in response to hyperosmolal stimuli such as diabetic ketoacidosis (DKA). Objective Characterize kinetics of copeptin and osmolality, and their dynamic relationship during rehydration and insulin therapy in children with type 1 diabetes (T1D) and DKA. Design and Setting Prospective o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
18
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(20 citation statements)
references
References 24 publications
2
18
0
Order By: Relevance
“…These differences were explained by the duration of diabetes and its known effects on osmoreceptor sensibility and on shifting the osmotic set point. 36,37 Our results confirm the findings of Burckhardt and colleagues, as children with newly diagnosed T1D in our study showed significantly higher copeptin concentration at 12-24 h than those with known T1D. Furthermore, metabolic acidosis interferes with vasopressin antidiuretic effects with a compensatory increase in vasopressin secretion by the neurohypophysis.…”
Section: Discussionsupporting
confidence: 91%
See 3 more Smart Citations
“…These differences were explained by the duration of diabetes and its known effects on osmoreceptor sensibility and on shifting the osmotic set point. 36,37 Our results confirm the findings of Burckhardt and colleagues, as children with newly diagnosed T1D in our study showed significantly higher copeptin concentration at 12-24 h than those with known T1D. Furthermore, metabolic acidosis interferes with vasopressin antidiuretic effects with a compensatory increase in vasopressin secretion by the neurohypophysis.…”
Section: Discussionsupporting
confidence: 91%
“…They also found that children with newly diagnosed T1D had higher concentrations of copeptin than those with known T1D after 12 h of DKA onset. These differences were explained by the duration of diabetes and its known effects on osmoreceptor sensibility and on shifting the osmotic set point 36,37 . Our results confirm the findings of Burckhardt and colleagues, as children with newly diagnosed T1D in our study showed significantly higher copeptin concentration at 12–24 h than those with known T1D.…”
Section: Discussionsupporting
confidence: 91%
See 2 more Smart Citations
“…Additionally, DKA has also been associated with early tubulopathy that may be caused by dysregulation of uric acid and vasopressin (58)(59)(60)(61)(62). Indeed, a recent study by Burckhardt et al found that copeptin, a surrogate marker for vasopressin, was elevated in children with DKA (63). Elevated copeptin concentrations have also been associated with markers of tubular injury and an increased risk for the development of DKD (62,64).…”
Section: Pathophysiologic Mechanisms Of Aki In Youth With Diabetesmentioning
confidence: 99%